2012
DOI: 10.3844/ajisp.2012.179.190
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-Associated Suppression of the Dendritic Cell Lines DC2.4 and Jawsii

Abstract: Dendritic cells function as potent regulators of both innate and adaptive immunity to tumors and the regulatory activities of these cells are tightly linked to their maturation and activation status. Despite the critical role played by dendritic cells in the induction of anti-tumor immune responses, the number of dendritic cells that can be isolated from experimental animals is limiting and often precludes in-depth analyses of these cells. To overcome this limitation, dendritic cell lines have been established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Therefore, to overcome the limitations inherent with studying the influence of tumors on DC function in both in vivo and ex vivo settings, DC lines that can be maintained as highly pure populations in culture have been generated and are a useful tool for in vitro studies aimed at understanding the basic biology of these cells (102105). Such lines have enabled direct analyses of tumor/DC interactions, and it has recently been shown that melanoma-derived factors suppress the LPS-induced maturation of both the DC2.4 and JAWSII DC lines (106). In a related study, a comparative analysis of multiple murine melanoma cell lines demonstrated that the suppression of DC2.4 costimulatory molecule and proinflammatory cytokine/chemokine expression correlates with the tumorigenicity of the melanoma under study (107), with the highly tumorigenic B16 melanoma exhibiting significantly greater suppression than its poorly tumorigenic, chemically mutated variant D5.1G4.…”
Section: Tumor-associated Suppression Of the Maturation And Activatiomentioning
confidence: 99%
“…Therefore, to overcome the limitations inherent with studying the influence of tumors on DC function in both in vivo and ex vivo settings, DC lines that can be maintained as highly pure populations in culture have been generated and are a useful tool for in vitro studies aimed at understanding the basic biology of these cells (102105). Such lines have enabled direct analyses of tumor/DC interactions, and it has recently been shown that melanoma-derived factors suppress the LPS-induced maturation of both the DC2.4 and JAWSII DC lines (106). In a related study, a comparative analysis of multiple murine melanoma cell lines demonstrated that the suppression of DC2.4 costimulatory molecule and proinflammatory cytokine/chemokine expression correlates with the tumorigenicity of the melanoma under study (107), with the highly tumorigenic B16 melanoma exhibiting significantly greater suppression than its poorly tumorigenic, chemically mutated variant D5.1G4.…”
Section: Tumor-associated Suppression Of the Maturation And Activatiomentioning
confidence: 99%
“…Because of the importance of DC maturation and activation in the induction and regulation of host immunity, we wished to study how tumor‐derived factors might influence these processes and the overall function of tissue‐resident DCs. We have previously shown that melanoma‐derived factors suppress costimulatory molecule expression and alter proinflammatory cytokine/chemokine production by the DC lines DC2.4 and JAWSII 22 , 23 . Moreover, the extent to which these phenomena were observed correlated with the tumorigenicity of the melanoma under study, as the highly aggressive B16‐F1 melanoma altered DC function to a significantly greater extent than the poorly tumorigenic D5.1G4 mutated variant.…”
Section: Resultsmentioning
confidence: 89%
“…Still less is known about tumor‐altered DC function in the context of melanoma, even though many protein‐, peptide‐ and DNA‐based vaccination strategies used to treat melanoma patients rely on the processing and presentation of tumor Ag by endogenous DCs whose maturation and activation are likely to be influenced by factors in the local tumor microenvironment 21 . Importantly, we have recently demonstrated in an in vitro model system that melanoma‐derived factors suppress the maturation and activation of the DC lines DC2.4 and JAWSII and that the extent of this suppression correlates with the tumorigenicity of the melanoma under study, with the highly aggressive B16‐F1 melanoma suppressing DC maturation and activation to a significantly greater extent than the poorly tumorigenic D5.1G4 melanoma, a chemically mutated variant of B16 that grows with much slower kinetics and spontaneously regresses in a large percentage of hosts 22 , 23 , 24 . Although these findings highlight the potential significance of tumor/DC interactions in the regulation of anti‐tumor immunity and tumor outgrowth, it is unclear how maneuvers used to immortalize DC lines influence their immunologic responsiveness, and much remains to be learned about the impact that tumor‐derived factors have on the function of naturally occurring DC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α activates sensory neurons directly via its receptors and initiates a cascade of inflammatory reactions through the production of ILs such as IL-1 and IL-6 (Hargadon et al, 2012) . At low concentrations in tissues, TNF-α has been called a guard cytokineas it initiates the defense response to local injury and augment of host defense mechanisms against infection (Feldmann and Steinman, 2005).…”
Section: Introductionmentioning
confidence: 99%